Ukrainian scientific-practical conference on the Day of science "Development of legal science, law-making and law enforcement in the period of independence of Ukraine" (May 12, 2011, Kyiv) - Сопілко, Ірина Миколаївна; Великанова, Марина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
With independence for Ukraine was a question of establishing a sustainable, sustainable human development, the creation and use of advanced technologies, the implementation of investment programs.